Clinical Outcomes of N3 Breast Cancer: A Real-World Study of a Single Institution and the US Surveillance, Epidemiology, and End Results (SEER) Database - Ai X; Liao X; Li J; Tang P; Jiang J (Cancer Management and Research, 2020)
Xiang Ai,1 Xin Liao,1 Junyan Li,2 Peng Tang,1 Jun Jiang1 1Breast Disease Center, Southwest Hospital, The Army Military Medical University, Chongqing 400038, People’s Republic of China; 2Department of Breast Surgery, People’s Hospital of DeYang City, Deyang 618000, People’s Republic of ChinaCorrespondence: Jun Jiang; Peng TangBreast Disease Center, Southwest Hospital, The Army Military Medical University, 30 Gaotanyan Road, Chongqing 400038, People’s Republic of ChinaEmail jcbd@medmail.com.cn; tp1232000@sina.comBackground: Although stage IIIC (any TN3M0) breast cancer is known to have a dismal prognosis, the clinical outcome of current standard management and the prognostic differences between N3a, N3b and N3c remain to be further investigated.Material and Methods: Data from our center on pathologic N3 (pN3) (n=284) breast cancer and the US Surveillance, Epidemiology, and End Results (SEER) database on clinical N3 (cN3) (n=15,291) and M1 (n=23,623) breast cancer between January 2004 and December 2015 were systematically analyzed for clinicopathological characteristics and survival outcomes.Results: In our institution, patients with pN3c had the worst survival, with 5-year OS and DFS rates of 52.4% and 41.5%, respectively. Patients with pN3b had a relatively good prognosis, with a 5-year OS rate of 75.3% vs 63.9% for the pN3a group (p=0.045). For DFS, the 5-year survival rate was 63.1% in the pN3b group compared with 40.3% in the pN3a group (p=0.030). In the US SEER database, patients with cN3c had the worst survival in the cN3 group, but the prognosis of cN3c was much better than that of M1. Similarly, patients with cN3b had a better prognosis compared with patients in other groups, with a 5-year OS rate of 68.9% vs 61.9% for the cN3a group (p< 0.001) and a 5-year BCSS rate of 73.4% vs 67.1% for the cN3a group (p< 0.001).Conclusion: Breast cancer patients with N3c had the worst clinical outcomes, while the prognosis of N3b patients was better than that of N3a patients.Keywords: breast cancer, N3, stage IIIC, survival